The Role of the Digital Terrain Models in the Assessment of Surplus Water Risk at the Szolnok-Túri Plain - Tóth, Károly; Tamás, János; Bíró, Tibor (Acta Agraria Debreceniensis, 2006)
The environmental factors to which surplus water can be assigned (topography, soil, groundwater, vegetation etc.) can be subject to special analysis and the randomness of the occurrences can be limited. The results of these procedures are surplus water risk maps of the areas, which can be utilised in land use planning. The risk map of the research site was created with overlaying digital category maps of the determining factors (hydraulic conductivity, convexity, critical probability of ground water level and land use).